Peroxidase-like Activity of CeO2 Nanozymes: Particle Size and Chemical Environment Matter - Arina D. Filippova; Madina M. Sozarukova; Alexander E. Baranchikov; Sergey Yu. Kottsov; Kirill A. Cherednichenko; Vladimir K. Ivanov (Molecules, 2023)
The enzyme-like activity of metal oxide nanoparticles is governed by a number of factors, including their size, shape, surface chemistry and substrate affinity. For CeO2 nanoparticles, one of the most prominent inorganic nanozymes that have diverse enzymatic activities, the size effect remains poorly understood. The low-temperature hydrothermal treatment of ceric ammonium nitrate aqueous solutions made it possible to obtain CeO2 aqueous sols with different particle sizes (2.5, 2.8, 3.9 and 5.1 nm). The peroxidase-like activity of ceria nanoparticles was assessed using the chemiluminescent method in different biologically relevant buffer solutions with an identical pH value (phosphate buffer and Tris-HCl buffer, pH of 7.4). In the phosphate buffer, doubling CeO2 nanoparticles’ size resulted in a two-fold increase in their peroxidase-like activity. The opposite effect was observed for the enzymatic activity of CeO2 nanoparticles in the phosphate-free Tris-HCl buffer. The possible reasons for the differences in CeO2 enzyme-like activity are discussed.